TMEPAI/PMEPA1 Is a Positive Regulator of Skeletal Muscle Mass - Hagg, Adam; Kharoud, Swati; Goodchild, Georgia; Goodman, Craig A.; Chen, Justin L.; Thomson, Rachel E.; Qian, Hongwei; Gregorevic, Paul; Harrison, Craig A.; Walton, Kelly L. (Frontiers in Physiology, 2020)
Inhibition of myostatin- and activin-mediated SMAD2/3 signalling using ligand traps, such as soluble receptors, ligand-targeting propeptides and antibodies, or follistatin can increase skeletal muscle mass in healthy mice and ameliorate wasting in models of cancer cachexia and muscular dystrophy. However, clinical translation of these extracellular approaches targeting myostatin and activin has been hindered by the challenges of achieving efficacy without potential effects in other tissues. Toward the goal of developing tissue-specific myostatin/activin interventions, we explored the ability of transmembrane prostate androgen-induced (TMEPAI), an inhibitor of TGF-β1-mediated SMAD2/3 signalling, to promote growth, and counter atrophy, in skeletal muscle. In this study, we show that TMEPAI can block activin A, activin B, myostatin and GDF-11 activity in vitro. To determine the physiological significance of TMEPAI, we employed Adeno-associated viral vector (AAV) delivery of a TMEPAI expression cassette to the muscles of healthy mice, which increased mass by as much as 30%, due to hypertrophy of muscle fibres. To demonstrate that TMEPAI mediates its effects via inhibition of the SMAD2/3 pathway, tibialis anterior muscles of mice were co-injected with AAV vectors expressing activin A and TMEPAI. In this setting, TMEPAI blocked skeletal muscle wasting driven by activin-induced phosphorylation of SMAD3. In a model of cancer cachexia associated with elevated circulating activin A, delivery of AAV:TMEPAI into tibialis anterior muscles of mice bearing C26 colon tumours ameliorated the muscle atrophy normally associated with cancer progression. Collectively, the findings indicate that muscle-directed TMEPAI gene delivery can inactivate the activin/myostatin-SMAD3 pathway to positively regulate muscle mass in health and models of disease.